Pengasingan komponen antiserangga daripada rizom scaphochlamys (Zingiberaceae) - Jamayah, Haji Lasit (Universiti Malaysia Sarawak (UNIMAS), 2005)
Scaphochlamys kunstleri var. speciosa is species in the Zingiberaceae family. Rhizome from Scaphochlamys kunstleri var. speciosa was isolate for insecticidal constituent. Processes of isolation have done by column chromatograph. Fourier Transform Infrared spectrophotometer (FTIR) was used identification offunction group. Bioassay was tested for contact oftoxicity in component from rhizome of~.kunstleri var. speciosa. Tested of toxicity by concentration of 500Jjml, 50Jjml and 5Jjml extract from methanol contact with larvae Artemia salina test insecticidal constituent. However the concentration of 500Jjml showed medium toxicity.